PENGGUNAAN ARTIFICIAL INTELLIGENCE DALAM MENULIS TEKS IKLAN: STUDI KOMPARATIF BERDASARKAN GENDER - Kartika Kartika; Azis Azis; Sakaria Sakaria (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2026)
This study aimed to analyse the differences in advertising text writing skills between male and female Year 8 pupils at SMPN 22 Makassar following the use of Artificial Intelligence, and to examine whether the use of Artificial Intelligence narrowed or widened the gender gap in learning outcomes. The research method employed was a quantitative approach using a one-group pretest-posttest design. The sample comprised 32 pupils selected via purposive sampling. The instrument, in the form of an advertising text writing test, was analysed using descriptive and inferential statistics (normality, homogeneity, and independent sample t-tests) with the aid of SPSS version 25. The results of the study indicate that the use of Artificial Intelligence improved the average learning outcomes of both male and female students. Hypothesis testing showed that there was no significant difference between the writing skills of the two genders after using Artificial Intelligence. The implications of this study confirm that Artificial Intelligence can function as a levelling tool that minimises the influence of gender factors in writing instruction. Teachers are advised to integrate Artificial Intelligence adaptively and in a gender-equitable manner without replacing their primary role as facilitators